TYPOLOGY OF CHALLENGES IN TEACHING A FOREIGN LANGUAGE TO STUDENTS OF MILITARY SCHOOLS - Fayyoza Dadaboyeva Khikmatulloyevna (Лучшие интеллектуальные исследования, 2023)
Abstract: Although military- academic lyceums were established a few years ago, there are still some issues yet to be solved. This article will address to the typology of problems encountered when teaching a foreign language to military school students and explore potential solutions.